DIGITAL LEARNING ENVIRONMENT IN EDUCATIONAL INSTITUTIONS CREATION MODELS AND THEIR POSSIBILITIES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This study is dedicated to the analysis of models and their possibilities aimed at creating a digital learning environment in educational institutions. In the process of creating a digital educational environment, PEST and SWOT analysis technologies were used to ensure the compatibility of technological, pedagogical and methodical supplies. In the process of research, suitable digital environment models for educational institutions were determined and their efficiency indicators were evaluated. The results made it possible to determine the priorities, problems and opportunities in the implementation of the digital educational environment.